Evaluation of the current status of the eye lens radiation exposure in an Interventional Radiology department - Pugliese, Mariagabriella; Amatiello, Antonia; Correra, Marco; Stoia, Vincenzo; Cerciello, Vincenzo; Roca, Vincenzo; Loffredo, Filomena; Fiore, Francesco; La Verde, Giuseppe (La Medicina del Lavoro, 2018)
Background: Following recent epidemiological studies, which showed tissue reactions from ionizing radiation at significantly lower doses, the 2013/59 EURATOM Directive of 5th December 2013 lowered the limit on the equivalent dose to the eye lens from 150 mSv to 20 mSv per year. Therefore, as a precautionary measure, it is considered appropriate to perform a timely dose monitoring by using specific dosimeters. Objectives: Analysis of the current state of the eye lens exposures during interventional procedures. The survey aimed at assessing the degree of information available to the exposed workers as regards lowering the dose limit in Interventional Radiology departments of some hospitals in Campania (Southern Italy). Methods: The equivalent dose was assessed, over a period of 90 days, using specific Hp dosimeters(3), placed sideways with regard to prescription eye glasses. The level of awareness of the new dose limit among operators was assessed using a questionnaire. Results: The values of the equivalent dose to the lens of the eye for the I and II Operators were found to be